ENT300 Fundamentals of Entreprenuership Business Plan : Amante del Cafe / Mohd Zuhairi Bin Sepori...[et.al] - Sepori, Mohd Zuhairi; Jemali, Mohammad Tarmimie; Saharudin, Zainal Abidin; Padis, Franks Lither (2012)
Our company name is Amante del Café. The business has been decided on the form of four partnerships. Each partner has contributes certain amount of capital as agreed in our agreement. Our main business activity is to provide the finest high quality coffee with fair prices. We will open our café at Padungan, Sarawak and hopefully will be open by 1st January 2013. All partners are encourage and entitled to participate in all business management. We have agreed that MOHD ZUHAIRI BIN SEPORI is the General Manager and the Administration Manager. ZAINAL ABIDIN BIN SAHARUDIN is the Operational Manager. MOHAMMAD TARMIMIE BIN JEMALI is the Marketing Manager and FRANKS LITHER PADIS is the Financial Manager. The management team will be lead by the General Manager and the other manager will help in other process. The general manager is responsible in controlling, leading, organizing as well as plan the entire business. The administrative manager will responsible in doing for all jobs relating to office administration. The marketing manager will be responsible in preparing the marketing process which includes the process of identifying the target market., determining the market size, identifying the competitors, determining the market share, developing the sales forecast and marketing strategies. The operation of our business is controlled and monitored by the operation manager. This is where quality control and productivity will take place in order to improve the efficiency of the workers. Finally, the financial manager will be handle financial matters such as preparing for the budgets and financial statement for the each department. All the financial statement need to be taken care properly by our Financial Manager.